(untitled) (Quinto Sol, 2013)
This paper deals with some beliefs and attitudes produced by the victorious groups of the coup d´état that took place in October 1820. We attempt to show that after these violent political episodes, centralist sectors displayed a conciliatory rhetoric that can be traced in periodicals and in the messages announced by men with political and military power in the province. Such a rhetoric was accompanied by measures taken by the provincial executive power and they were intented to integrate some federal sectors recently defeated. This statement allows to question the idea that October winners started an intense revenge over defeated groups, which could be notice in the new miltary reforms where no former revolutionary would be included.